2021
DOI: 10.1016/j.eng.2021.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Profiles of Antibody Responses, Cytokines, and Survival of COVID-19 Patients: A Retrospective Cohort

Abstract: The longitudinal immunologic status of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected patients and its association with the clinical outcome are barely known. Thus, we sought to analyze the temporal profiles of specific antibodies, as well as the correlations between the antibodies, proinflammatory cytokines, and survival of patients with coronavirus disease 2019 (COVID-19). A total of 1830 laboratory-confirmed COVID-19 cases were recruited. The temporal profiles of the virus, antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
0
6
0
1
Order By: Relevance
“…A previous study only found a correlation with IL-12p70/IL33 and IgG seroconversion, which correlated with disease severity (39). However, another study hypothesized that IL-8 and overall, the inflammation acts as a mediator between the association of IgG antibodies and the clinical outcome (40).…”
Section: Discussionmentioning
confidence: 94%
“…A previous study only found a correlation with IL-12p70/IL33 and IgG seroconversion, which correlated with disease severity (39). However, another study hypothesized that IL-8 and overall, the inflammation acts as a mediator between the association of IgG antibodies and the clinical outcome (40).…”
Section: Discussionmentioning
confidence: 94%
“…A growing body of evidence shows that elevated IL-8 is upregulated early and remains elevated during the disease course of COVID-19 [ 10 , 28 ]. These elevated levels of IL-8 have been significantly associated with increased mortality and greater disease severity in patients, indicating that IL-8 plays a role in disease progression [ 10 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence shows that elevated IL-8 is upregulated early and remains elevated during the disease course of COVID-19 [ 10 , 28 ]. These elevated levels of IL-8 have been significantly associated with increased mortality and greater disease severity in patients, indicating that IL-8 plays a role in disease progression [ 10 , 28 30 ]. Considering these data, it is possible to speculate that decreased neutrophil recruitment to the lungs due to the CXCR1/2 blockade likely contributed to the improved clinical outcomes seen in this study by mitigating the severe and uncontrolled hyperinflammatory disease manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stronger antibody responses to SARS-CoV-2 contribute to improved survival, and a protective effect that is independent of the disease severity. Maintaining high IgM and IgG antibody levels may be an indicator of rapid recovery ( 28 ). Our results showed that patients with lower IgG and IgM antibody levels at the time of discharge were more likely to be re-positive, especially patients with lower levels of IgG antibodies.…”
Section: Discussionmentioning
confidence: 99%